A comunidade no mundo hipermoderno : um jeito de devolver a Deus o que é de Deus - Danelon, Ildomar Ambos (2016)
This Master’s thesis seeks to address the role of the ecclesial community in the middle of a reality that tends to individualism - the hypermodernity - especially now that the Conference of the Brazil's Bishops launches the document number 100, "Community of Communities; a new parish - pastoral conversion of the parish”. From the hyper era, Gilles Lipovetsky analyzes the time of the hypermodernity and the consequent hiper individualization of the society, resulting in a new configuration of the relationship between people and with the consumer goods. It is seen, in this analysis, supported by Jung Mo Sung, that there is an idolatry context of market in our time, creating a mystique and a culture of sacrifice from who doesn't contribute to this market logic. In contrast to this situation, it is resorted to the community as a way to overcome the death and the idolatry. it seeks the sociological concept of the community in Durkheim, Tönnies and Buber, getting to the Christian concept of itself. It remembers the beginnings of the Christian ecclesial community, its evolution and the current proposal made by the National Conference of the Brazil's Bishops, in the document 100. Finally, it seeks to talks about the future of the community and how to make it provides full life, eliminating idolatry and sacrifice.